Education in the United States A Brief Overview. - Office of Education (DHEW), Washington, DC.; Office of Education (DHEW), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
The summary version of "Progress of Education in the United States of America", is intended for use by educational policymakers abroad and for all persons who are interested in educational development in the United States. The report is presented in seven chapters. Chapter I identifies general principles of American public education, as expressed in the Constitution and state statutes. Chapter II outlines the structure and organization of elementary, secondary, and post-secondary education and emphasizes the importance of adult education programs. Chapter III reviews the educational roles of the federal and state governments. Chapter IV describes how school curricula are determined and developed and how entrance and graduation requirements are set. Chapter V examines teacher education programs and notes the widespread existence of inservice programs for teachers on all levels. Chapter VI discusses federal involvement in educational research and information services, bilingual and bicultural education, competency based education, and reading comprehension programs. The final chapter cites statistics related to enrollment, teachers and instructional staff, schools and school districts, high school and college graduates, school retention rates, and expenditures. Tables of data are presented in the appendix. (Author/DB)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, D.C. 20402 (price not available).
ERIC Note: Not available in hard copy from EDRS due to small type size of parts of the original document.
Educational level discussed: Adult Education.
Educational level discussed: Elementary Secondary Education.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Keywords: Adult Education; Comparative Education; Curriculum; Data Analysis; Educational Administration; Educational Development; Educational Facilities; Educational Finance; Educational Legislation; Educational Objectives; Educational Philosophy; Educational Policy; Educational Practices; Educational Principles; Educational Programs; Elementary Secondary Education; Foundations of Education; Government Role; Higher Education; State Programs; Statistical Analysis; Tables (Data); Teacher Education; United States; Books